2020
DOI: 10.3390/app10072548
|View full text |Cite
|
Sign up to set email alerts
|

Transient Study of Flow and Cavitation Inside a Bileaflet Mechanical Heart Valve

Abstract: A mechanical heart valve (MHV) is an effective device to cure heart disease, which has the advantage of long life and high reliability. Due to the hemodynamic characteristics of blood, mechanical heart valves can lead to potential complications such as hemolysis, which have damage to the blood elements and thrombosis. In this paper, flowing features of the blood in the valve are analyzed and the cavitation mechanism in bileaflet mechanical heart valve (BMHV) is studied. Results show that the water hammer effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…To investigate the dynamic characteristics of check valves, the common methods used by other researchers are the fluid–solid interaction (FSI) method, the dynamic mesh method [ 21 , 22 , 23 ], and the weighted-essentially non-oscillatory (WENO) method [ 37 , 38 ]. The dynamic mesh method is adopted in this study to solve the opening period of check valves.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the dynamic characteristics of check valves, the common methods used by other researchers are the fluid–solid interaction (FSI) method, the dynamic mesh method [ 21 , 22 , 23 ], and the weighted-essentially non-oscillatory (WENO) method [ 37 , 38 ]. The dynamic mesh method is adopted in this study to solve the opening period of check valves.…”
Section: Methodsmentioning
confidence: 99%
“…Li et al [22] used CFD methods to study the mechanism of cavitation in a bileaflet mechanical heart valve, which is a type of check valve. Lai et al [23] focused on the opening period of a dual disc check valve using CFD and experimental methods, and they proposed a correlation to estimate the start and endpoints of disc rotations. Farrell et al [24] proposed a method to calculate the required flow rate to achieve the fully open state or an intermediate opening of check valves, and their results can reduce the simulation work.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 6 ] studied the cavitation suppression method in a globe valve with a valve cage. Li et al [ 7 ] and Qian et al [ 8 ] focused on the cavitation inside a mechanical heart valve. Sreekala and Thirumalini [ 9 ] found that the sound pressure level could be reduced by adding the flow passage numbers in the valve cage of a globe valve.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for patients with such valves, life-long anticoagulation therapy is necessary [1,2,17,32,33]. These defects are caused by the non-physiological dynamics of the blood flow through the valve, the rigidity of the valve leaflets, the formation of intense vortex and jet flows, and the increased shear stresses [34][35][36]. Intensive backflows are formed in the gaps of the hinged joints of the leaflets and the base of the valve, which destroy the red blood cells and platelet shells.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive backflows are formed in the gaps of the hinged joints of the leaflets and the base of the valve, which destroy the red blood cells and platelet shells. Here thrombi are formed, which are attached to the valve leaflets in the area of stagnant flows near the hinged joints [2,34,37,38]. Cavitation areas with microbubbles in the blood flow are formed, during the closing of the leaflets of the mechanical valves due to a sharp decrease in pressure.…”
Section: Introductionmentioning
confidence: 99%